EDUKASI PENINGKATAN KESEHATAN FISIK DAN MENTAL DALAM KONDISI JAM KERJA YANG LAMA DI KLINIK CILAMAYA KULON KABUPATEN KARAWANG - Yuliana, Chaerani Tri; Darmawan, Wendi; Jumaedi, Jumaedi; Muhidin, Muhidin; Widhiantika, Wieke (LP2M STP Mataram, 2023)
This community service program aims to improve the physical and mental health of healthcare workers at Cilamaya Kulon Clinic, Karawang Regency, who are working under long working hours. Long working hours and high work pressure can lead to physical exhaustion, stress, and burnout, which in turn affect the quality of healthcare services. This program consists of several stages, including a needs survey, educational sessions on physical and mental health, as well as mentoring and evaluation of the implementation. The results of the program showed a 25% reduction in physical fatigue and a 30% decrease in burnout. Additionally, there was a significant improvement in the nutritional intake of healthcare workers after attending the program. Through an educational approach focused on ergonomics, stress management, and a healthy lifestyle, healthcare workers at Cilamaya Kulon Clinic are better equipped to manage their physical and mental health, ultimately improving the quality of healthcare services. This program is also in line with the Ministry of Health's regulations regarding health standards for medical personnel